1999
DOI: 10.1021/ac990373m
|View full text |Cite
|
Sign up to set email alerts
|

Subattomole-Sensitivity Microchip Nanoelectrospray Source with Time-of-Flight Mass Spectrometry Detection

Abstract: A microfabricated microfluidic device coupled with a nanospray tip for electrospray ionization of dilute solutions is described. The device has been interfaced with a time-of-flight mass spectrometer and evaluated for sensitive, high-speed detection of peptides and proteins. The electrospray voltage was applied through the microchip to the nanospray capillary that was attached at the end of a microfabricated channel. Fluid delivery rates were 20-30 nL min(-)(1) through the hybridized structure without any pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 24 publications
2
162
0
3
Order By: Relevance
“…Thus, Bings et al developed a method to obtain low deadvolume connectors, as small as 0.7 nL. 387 When the spray is generated from a transfer capillary, either a disposable nanospray emitter 388,389 or a fused-silica capillary transfer line can be inserted in the microchip. For the former, the ESI nozzle is usually made with a sharp, tapered capillary end from which the liquid sprays to produce small, well-defined droplets.…”
Section: Spraying From a Capillary Sprayer Attached To The Chipmentioning
confidence: 99%
“…Thus, Bings et al developed a method to obtain low deadvolume connectors, as small as 0.7 nL. 387 When the spray is generated from a transfer capillary, either a disposable nanospray emitter 388,389 or a fused-silica capillary transfer line can be inserted in the microchip. For the former, the ESI nozzle is usually made with a sharp, tapered capillary end from which the liquid sprays to produce small, well-defined droplets.…”
Section: Spraying From a Capillary Sprayer Attached To The Chipmentioning
confidence: 99%
“…Although the present work analyzed cells through nonspecific fluorescent labeling of amino acids, any of a myriad of optical probes might be used (29). Alternatively, the device might be mated to a mass spectrometer for analysis (30). This device could be used generally for applications that involve reactions and separations of picoliter volumes of liquids.…”
Section: Integrated Microfluidic Chip For Manipulation and Analysis Omentioning
confidence: 99%
“…11) It has been demonstrated that micro uidic chips attached with a capillary emitter can be used to carry out tryptic digestion for complex protein samples online. [12][13][14] Moreover, recent miniaturization devices used in the MS application have been focused on multiplexed MS analysis; for example, hundreds of thousands of micrometer scale compartments can be fabricated for high-throughput DNA analysis. 15) Arrays of microchannels have been used for infusion analysis of a variety of samples in connection with MS. 16) Recent developed atmospheric pressure ionization methods such as desorption electrospray ionization (DESI), 17) direct analysis in real time (DART), 18) electrospray-assisted laser desorption/ionization (ELDI), 19) an atmospheric solid analysis probe (ASAP), 20) laser diode thermal desorption (LDTD), 21) extractive electrospray ionization (EESI), 22) and laser spray 23) provide more options when coupling with micro uidic devices.…”
Section: Introductionmentioning
confidence: 99%